ANALISIS HUKUM TINDAK PIDANA TERHADAP TERDAKWA YANG MEMBERIKAN KETERANGAN PALSU UNTUK KEUNTUNGAN PRIBADI: PUTUSAN NOMOR 20/PID.B/2023/PN.GDT - Taufik Hidayat, Rizky; Fitriyantica, Agnes; Yuda Sudawan, Moh (Journal Evidence Of Law, 2023)
“This study is entitled legal analysis of criminal acts against defendants who give false statements for personal gain: decision Number 20 / Pid.B/2023 / PN.Gdt. with the formulation of the problem of how the application of Criminal Law laws against witnesses who give false statements and what are the factors that cause perpetrators to commit crimes in giving false information for personal gain based on Decision number 20/Pid.B/2023 / PN.Gdt. Using normative juridical methods. In conclusion, the factors that prompted the defendant to commit the crime of giving false information for his own sake, based on court decision number 20/Pid.B / 2023 / PN Gdt, is because the defendant gave false information in making a report on the loss of a motorcycle at the Tegineneng Police Station. The defendant did this because he was afraid that he would not be able to continue paying the monthly installments of the motorcycle that was still on credit in leasing, and the defendant intended that the police report he made could be used as the basis for an insurance” claim.